Fake law : the truth about justice in an age of lies - Secret Barrister (London : Picador, 2020)
Could the courts really order the death of your innocent baby? Was there an illegal immigrant who couldn't be deported because he had a pet cat? Are unelected judges truly enemies of the people? Most of us think the law is only relevant to criminals, if we even think of it at all. But the law touches every area of our lives: from intimate family matters to the biggest issues in our society. Our unfamiliarity is dangerous because it makes us vulnerable to media spin, political lies and the kind of misinformation that frequently comes from loud-mouthed amateurs and those with vested interests. This 'fake law' allows the powerful and the ignorant to corrupt justice without our knowledge - worse, we risk letting them make us complicit. Thankfully, the Secret Barrister is back to reveal the stupidity, malice and incompetence behind many of the biggest legal stories of recent years. In Fake Law, the Secret Barrister debunks the lies and builds a defence against the abuse of our law, our rights and our democracy that is as entertaining as it is vital.
Introduction -- Yourself and your home -- Your family -- Your health -- Your work -- Our human rights -- Our access to justice -- Our liberty -- Equality and due process -- Democracy -- Epilogue: our future.
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of -- Great Britain